2023
DOI: 10.4103/abr.abr_383_21
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Coronary Artery Disease Based on Machine Learning Algorithms Support Vector Machine, Artificial Neural Network, and Random Forest

Abstract: Background: Coronary artery disease (CAD) is known as the most common cardiovascular disease. The development of CAD is influenced by several risk factors. Diagnostic and therapeutic methods of this disease have many and costly side effects. Therefore, researchers are looking for cost-effective and accurate methods to diagnose this disease. Machine learning algorithms can help specialists diagnose the disease early. The aim of this study is to detect CAD using machine learning algorithms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The study conducted by Ayatollahi H et al [34], aimed at comparing the performance of SVM and ANN models in predicting CAD, showed that the accuracy of SVM model is higher than that of ANN model. Similarly, the study by Saeedbakhsh S et al [35], which aimed at detecting CAD using machine learning algorithms, showed that the accuracy of SVM was 88.8% and for ANN it was 88.5%. In Kumar R et al [36].…”
Section: <> Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The study conducted by Ayatollahi H et al [34], aimed at comparing the performance of SVM and ANN models in predicting CAD, showed that the accuracy of SVM model is higher than that of ANN model. Similarly, the study by Saeedbakhsh S et al [35], which aimed at detecting CAD using machine learning algorithms, showed that the accuracy of SVM was 88.8% and for ANN it was 88.5%. In Kumar R et al [36].…”
Section: <> Discussionmentioning
confidence: 88%
“…Our ndings indicate that the sensitivity for predicting CAD is higher for SVM and ANN models compared to the LR model, but SVM and ANN models are equal. In Nusinovici [35] showed that the sensitivity of SVM and ANN models was 0.574 and 0.582, respectively. These results are similar to our ndings and indicate that SVM and ANN models have similar sensitivity indices.…”
Section: <> Discussionmentioning
confidence: 99%